Pengaruh E-service quality dan E-Trust terhadap E-loyalty Pengguna Simobiplus dengan E-Satisfaction sebagai Variabel Mediasi - Ciandi, Wiliam Yanto (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The increase in the transaction values and volumes of electronic money is a phenomenon showing that people tend to use electronic payment methods, such as mobile banking. Based on a survey entitled Bank Service Excellence Monitor of 2022, SimobiPlus is one of the ten best performing mobile banking of the year. However, despite the numerous awards in digital service development, users were still complaining about the service of SimobiPlus in both Appstore and Playstore, and this might affect their loyalty. The objective of this research is to analyze the effect of e-service and e-trust on the e-loyalty of SimobiPlus users through the mediation of e-satisfaction. Using non-probability sampling method and purposive sampling technique, 121 SimobiPlus users living in Malang city were selected as the samples. The results of the Partial Least Squares analysis indicate that e-service quality, e-trust, and e-satisfaction positively and significantly influence e-loyalty, that e-service quality and e-trust positively and significantly affect e-satisfaction, and that e-satisfaction significantly mediates the impact of e-service quality and e-trust on e-loyalty. This research is particularly directed to Bank Sinarmas. The fierce competition in banking industry requires Bank Sinarmas to continuously provide excellent services to its customers through serving their needs. Abstrak Fenomena peningkatan nilai dan volume transaksi penggunaan uang elektronik, menunjukkan masyarakat cenderung menggunakan metode pembayaran elektronik, seperti mobile banking. Disamping banyaknya penghargaan, beberapa nasabah juga memberikan komentar negatif terkait layanan SimobiPlus melalui appsstore maupun playstore. Tujuan penelitian ini adalah menganalisis pengaruh E-service quality dan E-Trust terhadap e-loyalty pengguna SimobiPlus dengan E-Satisfaction sebagai variabel mediasi. Metode analisis yang digunakan adalah analisis Partial Least Square. Penentuan sampel dalam penelitian ini menggunakan metode non-probability sampling dengan teknik purposive sampling. Sampel terdiri dari 121 pengguna SimobiPlus berdomisili Kota Malang. Hasil temuan dari studi ini menunjukkan bahwa e-service quality, E-Trust, dan E-Satisfaction secara positif dan signifikan mempengaruhi e-loyalty. E-service quality dan E-Trust secara positif dan signifikan mempengaruhi E-Satisfaction. Selain itu, penelitian ini juga menunjukkan E-Satisfaction secara signifikan memediasi pengaruh E-service quality dan E-Trust terhadap e-loyalty pengguna SimobiPlus. Implementasi dari penelitian ini lebih ditujukan untuk Bank Sinarmas. Persaingan yang ketat di industri perbankan mengharuskan Bank Sinarmas untuk selalu memberikan pelayanan prima terhadap nasabah Bank Sinarmas dalam hal melayani kebutuhan nasabah.